Status and spatial ecology of a large carnivore guild in a heterogeneous, multiple-use landscape: Implications for conservation in modern African settings - Strampelli, P (2021)
Understanding the ecology of large carnivores in increasingly complex, multi-use conservation landscapes is crucial for their effective conservation in 21st century Africa, as is determining which management strategies can reconcile conservation with economic growth and human development. Reliable population monitoring techniques are essential to achieve both these goals. This thesis aims to address key knowledge gaps in the above themes, through a study of an intact large carnivore guild in Tanzania’s Ruaha-Rungwa landscape. First, I apply occupancy modelling to sign-based data to investigate the distribution and habitat use of large carnivores, their prey, and human activity across the complex, at multiple spatial scales (Chapter 3). I show that species are limited by anthropogenic, management, and biotic factors, revealing the importance of integrated research and conservation planning for large carnivore management. I also identify a novel threat to Tanzania’s biodiversity, in the form of increased habitat degradation associated with trophy hunting block abandonment. To investigate interspecific interactions within the large carnivore guild, I then apply conditional co-occupancy models to the same dataset, again for multiple species and at multiple scales (Chapter 4). I find that African wild dog (Lycaon pictus) avoid lion (Panthera leo) at both coarser and finer spatial scales, with effects being strongest in disturbed areas. Findings indicate that interspecific pressures can have a strong influence on the habitat use of large carnivores in multi-use landscapes, and must be appreciated in conservation planning. To then complement these insights with finer-scale metrics, I apply spatially explicit capture-recapture (SECR) models to camera trap data to investigate the effects of habitat and land management strategies on lion population density (Chapter 5). Lion exist at highest densities in well-protected, prey-rich environments, including in community-managed areas, and at intermediate densities in miombo woodlands and in trophy hunting areas. I show that the method employed has the potential to be an important tool for lion population management. In Chapter 6, I use a range of data to provide insights into the status of Ruaha-Rungwa’s cheetah (Acinonyx jubatus) population. Findings reveal an extension of known geographical range for the species, and provide some of the first evidence that miombo woodlands may be important for cheetah across its eastern African range. I also show that collaborations with tourism operators hold potential for cheetah population monitoring, and I identify regional research priorities for the species. Finally, I contextualise my findings by reviewing two decades of peer-reviewed African large carnivore population assessments, and identifying trends, biases, and opportunities in research (Chapter 7). I find that studies are biased towards southern and eastern Africa, particularly South Africa and Kenya, and that population assessments are significantly positively biased towards lion, and significantly negatively biased against striped hyaena (Hyaena hyaena). Most populations are understudied, and opportunities exist for research on most species and in most countries, and for increased inclusion of local authors and capacity building in range countries. Overall, the collective findings of this thesis highlight the necessity for increasingly integrated and synthetic research, as heterogeneity and complexity of conservation systems increases, and for an increased appreciation of the effects of anthropogenic impacts on large carnivores, even within protected areas. They also show that conserving large carnivore guilds will require robust population monitoring, and, more broadly, a shift towards more inclusive approaches to conservation that can secure wildlife without sacrificing human well-being and socio-economic development.